Respon Mahasiswa Terhadap Impelementasi Pembelajaran Berbasis Riset Pada Topik Aliran Fluida - Gunarjo Suryanto Budi; Fenno Farcis; Theo Jhoni Hartanto; Umi Amanda Putri; Kristanoval Siloam (Jurnal Ilmiah Kanderang Tingang, 2024)
Physics subjects are one of the subjects that can develop analytical, critical, inductive and deductive abilities in solving problems through scientific activities. However, several research results show that physics is a subject that is less popular because most students consider physics to be abstract, difficult to understand, and not related to life, which has an impact on students' low understanding of physics. This research aims to describe student responses to research-based learning on fluid flow material. The participants were students in the second year of the Physics Education Study Program, FKIP, Palangka Raya University, consisting of 20 people taking the Thermodynamics lecture. The instrument used is a questionnaire response to a concept understanding test. The research results showed that students responded positively to the research-based learning they had participated in. Based on this research, research-based learning activities can be considered as an alternative for carrying out meaningful learning activities, especially in physics learning.